They Were There - Douglass, Herbert E.; Nang Chan Yeema (Nampa, Idaho, United States Pacific Press Publishing Association, 2005)
They were there: stories of those who witnessed Ellen White's Prophetic gift and believed/Herbert Edgar Douglass.
Keywords: Adult Nonfiction